(untitled) (Journal of Business and Technology (Dhaka), 2016)
The aims of this study are to evaluate the financial performance of Islamic and conventional banks of Bangladesh through CAMEL test during the period of 2009 to 2013. The study tries and to determine whether there are significant differences between the two categories of banks for each of the ratios used in CAMEL test. A sample of five listed conventional banks and five listed Islamic banks were selected to study the objectives. The data used in this study were compiled from the financial statements of the respective sample banks. To make substantial noteworthy results, t-test(independent sample) is used. This paper found no significant difference between the Islamic banks and conventional banks regarding capital adequacy, management capability and earnings but found a significant difference regarding asset quality. Journal of Business and Technology (Dhaka) Vol.10(1) 2015; 73-91